The recognition of affective states associated with players' non-verbal behavior in volleyball. (January 2023) - Fritsch, Julian; Ebert, Stephanie; Jekauc, Darko
Abstract: The visible non-verbal behavior of volleyball players after a point might indicate their affective state. The purpose of the present study was to investigate whether the point outcome (i.e., win vs. loss) and the importance of the situation (i.e., first vs. fifth set) influence how well the affective states (indexed through non-verbal behavior) can be recognized. For this purpose, 111 participants were presented 60 video excerpts showing the non-verbal behavior of volleyball teams immediately after a rally and asked whether the shown team had just won or lost a point. The results indicated that the recognition rate was significantly higher for won (80.09%) than for lost points (65.56%) as well as for points of the fifth set (77.84%) than for points of the first set (68.51%). Furthermore, an explorative analysis showed that the recognition rate was significantly higher for won points of the fifth set (89.19%) than for those of the first set (72.13%). Highlights: Video excerpts used to assess recognition of affective states in volleyball teams. Higher recognition rates after won than after lost points. Higher recognition rates after points in the fifth than in the first set. Recognition rates highest for won points in the fifth set.